INTERPRETATION OF THE CATEGORY OF PERFECT HUMAN BEING IN THE TEACHINGS OF OUR GREAT ANCESTORS (International Conference on Modern Science and Scientific Studies, 2025)
This article mainly cites the fact that information about our great ancestors has been studied by scientists, orientalists, philosophers, literary critics, educators, sociologists, and even psychologists. Historical sources, manuscripts, and primary sources about the perfect man have been analyzed. The source is the very antiquity of Sufism, which is the basis of the teachings of Sufism, and its history to this day.